2021
DOI: 10.1021/acs.jmedchem.0c02237
|View full text |Cite
|
Sign up to set email alerts
|

Stapled Wasp Venom-Derived Oncolytic Peptides with Side Chains Induce Rapid Membrane Lysis and Prolonged Immune Responses in Melanoma

Abstract: Peptide stapling chemistry represents an attractive strategy to promote the clinical translation of protein epitope mimetics, but its use has not been applied to natural cytotoxic peptides (NCPs) to produce new oncolytic peptides. Based on a wasp venom peptide, a series of stapled anoplin peptides (StAnos) were prepared. The optimized stapled Ano-3/3s were shown to be protease-resistant and exerted superior tumor cell-selective cytotoxicity by rapid membrane disruption. In addition, Ano-3/3s induced tumor abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Further, our toxicity assays ( Figures 3A , B , Table 3 ; Supplementary Figures 16 , 17 ) and previous works ( Chapuis et al, 2012 ; Wu et al, 2021 ) support that changing a charged amino acid to S 5 increases the toxicity of peptide analogs. For peptides with a lower positive charge than the natural anoplin, we observed a dose-dependent reduction in cell viability and increased hemolytic activity.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further, our toxicity assays ( Figures 3A , B , Table 3 ; Supplementary Figures 16 , 17 ) and previous works ( Chapuis et al, 2012 ; Wu et al, 2021 ) support that changing a charged amino acid to S 5 increases the toxicity of peptide analogs. For peptides with a lower positive charge than the natural anoplin, we observed a dose-dependent reduction in cell viability and increased hemolytic activity.…”
Section: Discussionsupporting
confidence: 87%
“…The staple location sites were selected to reduce toxicity and improve the antibacterial activity of anoplin but at the same time to keep its amphipathic character ( Figure 1A ). Previous research showed that substituting anoplin positively charged amino acids (Lys and Arg) with staples increased its oncological activity in cellular models and mouse tumor models ( Wu et al, 2021 ). Thus, we expected that Lys and Arg modifications would increase anoplin toxicity against eukaryotic cells.…”
Section: Resultsmentioning
confidence: 99%
“…MP exhibited potent antitumor activity because of the interaction between its cationic amphipathic α-helical region and tumor cell membranes 17 , 18 . In order to enhance its oncolytic potency and resistance to enzyme degradation, an all-hydrocarbon stapling strategy was used to induce a stable α-helical structure 13 . To identify MP derivative(s) with an optimal therapeutic index (TI), we incorporated two ( S )-pentenyl alanine residues (S 5 ) at the i and i + 4 positions of MP to obtain a staple-scanning library by Fmoc solid-phase peptide synthesis (SPPS) 19 , 20 and evaluated their secondary structure features, anti-proliferative, and hemolytic activities (Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsic shortcomings of current oncolytic peptides include structural instability, proteolytic susceptibility, and suboptimal antitumor activity. To overcome these drawbacks, we developed a series of wasp venom-derived oncolytic peptides by peptide stapling technology, which significantly improved the α-helical stabilization and anti-tumor effects of parent peptide in B16F10 tumor-bearing mice 13 . However, the requirement for intratumoral administration limits the application of these oncolytic peptides towards both large and metastatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the peptide structural context, several cyclization strategies can be applied: head-to-tail, side chain-to-head, side chain-to-tail and side chain-to-side chain [5]. A plethora of chemistries have been developed for cyclization, ranging from natural disulfide bridges or isopeptide bonds to metal-catalyzed ring-closing metathesis (RCM), as well as azide-alkyne and Diels-Alder cycloadditions [26,27]. Moreover, peptide conformations may be further constrained by multicyclization and the use of chemical scaffolds to mediate linkage [28].…”
Section: Cyclizationmentioning
confidence: 99%